ASSESSMENT OF HEAVY METAL POLLUTION AND CONTAMINATION IN WASTE DUMPSITES WITHIN GUSAU AREA, NORTHWEST NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The aims of this research work are to determine the concentrations of metals present in waste dump soils, to evaluate the metal contamination of the soils using the pollution indices and to identify whether the sources of heavy metals were natural and/or anthropogenic. Analysis of the soil was carried out using EDXRF technique. Three points were assessed from each three wastes dumpsites (Hira Dekodi, Low Cost and Old Market), using portable XRF equipment for the in-situ data acquisition. The data obtained were subjected to statistical analysis and environmental pollution index models. The data showed mean concentrations of the heavy metals analyzed in the following order Fe > Zn > Mn > Cr > Pb > Ni. The mean concentrations of these three metals (Pb, Zn and Cu) exceeded their average crustal abundance, which is an indication of possible contamination. Environmental pollution models applied to the geochemical dataset revealed Zn, Pb and Cu as considerable/moderately contaminated, which generally indicated severe potential contamination in the investigated area. Other metals such as Mn, Cr, Ni and Fe showed low contamination factors. However, from the results of geo-accumulation/ecological risk index of the heavy metals, the study areas were unpolluted and indicated low ecological risk factors with respect to the analyzed parameters. The chemical assay revealed positive and significant relationship between Cu, Pb, Mn and Fe while Cr showed positive and significant relationship with Mn, Fe and Cu. However, Zn shows significant level of relationship only to Mn. Virtually, all the heavy metals showed...
Keywords: Heavy Metals; Ecological Risk Factor; Pollution index; Health impact; Dumpsites